Key to the Oriental species of Passaloecus Shuckard (Hymenoptera: Crabronidae), with descriptions of four new species from China - Ma, Li; Li, Qiang (Zootaxa, 2012)
A key to the Oriental species of Passaloecus Shuckard (Crabronidae: Pemphredoninae: Pemphredonini) is provided. Four new